Seamen, Surgeons and Empire: Spanish Naval Medical Reform and Mexican Medicine in the Late Colonial Period - Hernández-Sáenz , Luz María (The Northern Mariner / Le marin du nord, 2000)
Como la curación, y asistencia de los Enfermos sea uno de los mas recomendables objetos que han merecido el cuidado del Rey, por lo que interesa su Real servicio, y por la piedad con que su Soberana clemencia propende siempre al desempeño de tan sagrada atención, sin perdonar gasto alguno, dirigido al restablecimiento de la salud que han perdido, dispuso S.M. se erigiesen en America Hospitales de cuenta de su Real Hacienda...1 (As the treatment and care of the ill is one of the most commendable objectives that has merited the attention of the King, in the interest of his royal service, and given his mercy and sovereign clemency that prevail always in the fulfilment of such sacred tasks, without sparing any expense to restore the lost health of the ill, H.M. ordered the erection of hospitals in North America to be funded by his Royal Treasury.)